Genes, in context How Life Works: A User's Guide to the New Biology Philip Ball University of Chicago Press, 2023. 552 pp - Goldman, Michael A (Science (American Association for the Advancement of Science), 2024)
As biologists have long known, the genome is only one piece in the puzzle of life.